Performance determinants in tropical trail running: Race result analysis of the 5K and 10K Merapi Merbabu de Trail 2025 - Siti Baitul Mukarromah; Sugiarto Sugiarto; Gustiana Mega Anggita; Sri Agus Budi Santoso; Sangheon Park; Ambar Dwi Erawati; Rikha Liemiyah; Aziiz Mardanarian Rosdianto; Ronny Lesmana; Faisyal Syofian (CV Rezki Media, 2026)
Background: The limited research on the determinants of performance in short-distance trail running in tropical environments is a major problem in understanding the influence of environmental conditions on runners' performance and pacing strategies.Objectives: This study aimed to examine the influence of race distance, sex, and age on trail running performance in the 5K and 10K categories of the Merapi Merbabu de Trail 2025.Methods: A retrospective observational race result analysis was conducted using official race data from the Merapi Merbabu de Trail 2025. The study included 429 runners (5K: n = 144; 10K: n = 285), consisting of 275 male and 154 female participants. The primary outcome variable was finish time (in minutes), while the independent variables included race, distance, sex, and age. Statistical analyses were performed using SPSS version 26, including descriptive statistics, independent-samples t-tests, Cohen’s d effect sizes, and multiple linear regression to evaluate predictors of performance.Results: Results showed a significant difference in performance between race distances. The mean finish time for the 5K category was 152.8 ± 44.3 minutes, while the 10K category averaged 306.1 ± 74.3 minutes (t = -26.68, p < 0.001, Cohen’s d = 2.50). Male runners completed the 10K race faster than female runners (293 vs. 345 minutes). Regression analysis indicated that finish time increased by approximately 2–3 minutes per year of age, indicating a progressive decline in performance with increasing age.Conclusions: These findings indicate that race distance, sex, and age are significant determinants of trail running performance in tropical environments.